The challenges and importance of good role leadership in Information Management / Akilah Nadirah Mohd Roszelin, Nur Anis Syuhada Ab Malek and Umi Nazirah Zainal - Mohd Roszelin, Akilah Nadirah; Ab Malek, Nur Anis Syuhada; Zainal, Umi Nazirah (Faculty of Information Management, 2014)
Leadership is the main key to the success or the failure of the organization. A good leader can influence their workers to follow their order without any objections. However, the leader should not only can give an instruction to their workers, but they should build a very good relationship with them to achieve an organization's goals. In addition, a great leader in any organization's management, should have an open communication because it can reduce the gap between the leader and their workers. Other than that, the leader will face many challenges in order to become great and respectful leader in their organizations. In information management, a leader play an important role to ensure their workers can differentiate between the facts and fake information.